Prinsip Dan Pengaturan Pelayanan Kesehatan Dalam Prespektif Hukum Nasional - Surya Makhdi Makas Sidabukke (Jurnal JURISTIC, 2025)
Healthcare services are part of citizens' constitutional rights. The existence of the right to healthcare services needs to be analyzed both in principle and legally to ensure optimal healthcare services. This article is a conceptual article that will attempt to analyze and examine the principles of healthcare services in Indonesia and the legal framework of healthcare services in Indonesia. The analysis results show that in healthcare practice, there are five main ethical principles: Nonmaleficence, Beneficence, Confidentiality, Justice, and Fidelity. In Indonesia, the right to healthcare services is guaranteed by the 1945 Constitution and regulated by Law Number 17 of 2023 on Healthcare, as well as government regulations. Healthcare services are based on these ethical principles, with a focus on care, justice, fidelity, and confidentiality, to create quality and equitable healthcare services for all.